Sustainability in Business: The Shift Toward Green Commerce in 2021 (International Journal of Food and Nutritional Sciences, 2021)
The transition toward green commerce in business practices has become a key area of focus in recent years, particularly in 2021, when sustainability emerged as a critical factor for business success. This paper explores the growing trend of sustainability in business, specifically within the context of India, where green commerce is becoming increasingly important. The research investigates the factors driving this shift, the impact of consumer preferences, corporate strategies for implementing sustainability, and the role of government policies. By analyzing data from consumer surveys, corporate sustainability reports, and government initiatives, this paper provides a comprehensive understanding of the shift toward sustainable business practices in India. Key findings reveal that the increasing demand for eco-friendly products, along with stricter regulations and the rise of corporate social responsibility, has significantly influenced businesses to adopt green strategies. However, challenges such as financial constraints and lack of awareness among small and medium enterprises (SMEs) persist, limiting the widespread adoption of green commerce practices. This paper concludes by discussing the opportunities for businesses to capitalize on the growing trend of green commerce and its potential to transform India’s economic and environmental landscape.